2008
DOI: 10.1063/1.2998696
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field-induced strain assisted by tensile stress in L1 martensite of a Ni–Fe–Ga–Co alloy

Abstract: Magnetic-field-induced strains larger than 2% have been obtained in the nonlayered L10 martensite of a Ni49Fe18Ga27Co6 single crystal, under an assisting tensile stress around 16 MPa and fields below 15 kOe. In martensitic samples previously compressed, application of a constant tensile stress along the same axis together with a perpendicular magnetic field produces the elongation of the sample, as one of the variants rotates its c axis from the field direction to the stress-axis direction. An estimated magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Among Heusler type FSMAs, the NiFeGaCo alloys represent (to date) the only known analog to classical NiMnGa in terms of a giant MFIS that they show [3,22]. Compared to NiMnGa, these materials are much more ductile (see [23] and references therein) whereby they are much more sustainable to SE cycling, which is an important advantage for their applications in elastocaloric devices [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Among Heusler type FSMAs, the NiFeGaCo alloys represent (to date) the only known analog to classical NiMnGa in terms of a giant MFIS that they show [3,22]. Compared to NiMnGa, these materials are much more ductile (see [23] and references therein) whereby they are much more sustainable to SE cycling, which is an important advantage for their applications in elastocaloric devices [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, Chernenko et al [48] recently observed a MFIS of ∼0.2% in NM martensite, clearly evidencing significant magnetic-field-induced twin boundary motion in NM martensite. Moreover, stress-assisted MFIS has also been successfully achieved in NM martensite [49], [50], [51], making it promising for practical applications. In fact, the NM martensite which is formed as a ground state of the Heusler-type FSMAs [48] has many advantages over 5M and 7M martensites, including high stability, good chemical properties and high ductility [48].…”
Section: Introductionmentioning
confidence: 99%
“…For calculation of the theoretical recoverable strains j3 CVP j and j3 CVPþdtw j, the following lattice parameters were used for the different phases: a 0 ¼ 0.576 (0.288) nm for L2 1 18 for 14M martensite and a ¼ 0.381 nm, c ¼ 0.327 nm for L1 0 -martensite in NiFeGa alloys [2,4]. Recent studies on NieFeeGaeCo alloys have shown that addition of Co to the NieFeeGa system does not significantly change the lattice parameters of austenite and the tetragonal L1 0 -martensite [11,12,15]. For the 14 M structure slightly different lattice parameters of a ¼ 0.420 nm, b ¼ 0.268 nm, c ¼ 2.915 nm, b ¼ 86.3 were determined for a Ni 49 Fe 18 Ga 27 Co 3 (at.%) alloy [16].…”
Section: Methodsmentioning
confidence: 99%